Pengaruh Environment, Social, & Governance (ESG) Terhadap Nilai Perusahaan Pada Sektor Pertambangan Yang Terdaftar Di ESG Leaders Indonesia Periode 2017-2022 - Devianti, Intan Putri (Universitas Negeri Surabaya, 2025)
This research aims to identify the factors influencing the firm value of mining companies listed on the Indonesia ESG Leader from 2017 to 2022. The study focuses on four independent variables: environment score, social score, governance score, and ESG combined score. Using purposive sampling, the sample consists of seven mining companies that have been consistently listed on the Indonesia ESG Leader index during the specified period. The data analysis technique applied in this study is panel data regression, which allows for examining the effects of these variables on firm value over time. The results indicate that the environment score, social score, governance score, and ESG combined score do not significantly influence the firm value of the companies in the sample. This suggests that the current efforts of mining companies in implementing environmental, social, and governance (ESG) practices may not have immediately tangible effects on their financial performance. One possible explanation is the high costs associated with ESG initiatives and the long time frame required to see measurable outcomes. Therefore, the research highlights the importance of maintaining consistency in ESG reporting, as continued adherence to ESG principles may help secure long-term support from consumers and investors, ultimately enhancing firm value in the future.